Achieving Amphibious Superprotonic Conductivity in a CuI Metal–Organic Framework by Strategic Pyrazinium Salt Impregnation. Issue 4 (13th December 2017) - Khatua, Sajal; Bar, Arun Kumar; Sheikh, Javeed Ahmad; Clearfield, Abraham; Konar, Sanjit
Abstract: Treatment of a pyrazine (pz)‐impregnated Cu I metal–organic framework (MOF) ([1⊃pz] ) with HCl vapor renders an interstitial pyrazinium chloride salt‐hybridized MOF ([1⊃pz⋅6 HCl] ) that exhibits proton conductivity over 10 −2 S cm −1 both in anhydrous and under humid conditions. Framework[1⊃pz⋅6 HCl] features the highest anhydrous proton conductivity among the lesser‐known examples of MOF‐based materials exhibiting proton conductivity under both anhydrous and humid conditions. Moreover, [1⊃pz] and corresponding pyrazinium sulfate‐ and pyrazinium phosphate‐hybridized MOFs also exhibit superprotonic conductivity over 10 −2 S cm −1 under humid conditions. The impregnated pyrazinium ions play a crucial role in protonic conductivity, which occurs through a Grotthuss mechanism. Abstract : Strategic single crystal to single crystal (SC–SC) transformation of a porous Cu I metal–organic framework (MOF) resulted in a pyrazinium salt‐impregnated hybridized MOF featuring the first example of superprotonic conductivity both in anhydrous and under humid conditions.